Procurement Corruption Risk Mitigation Strategies for Global Companies Investing in Developing Nations: A Vietnam Perspective - Kottmann, Hans-Joerg (Digital Repository of Theses, 2025)
Foreign companies investing in developing nations have their focus during the initial years of setting up operations on market development and therefore on the sales and marketing side. Generating turnover trumps cost efficiency. Careful external capital spending to develop and maintain operations is often neglected or at least potentials for savings are not identified early on. It is during this crucial period that an organization is most vulnerable to fraudulent behavior as well as victimhood to bribery attempts, and it is fundamental to eradicate such tendencies during the company culture forming years. This dissertation examined the specific situation for predominantly Europe-originating companies in Vietnam where corruption has been a long-standing problem in the country’s rapid economic development. By means of quantitative and, to a lesser degree qualitative methods, it has been evaluated to what degree organizational, procedural and corporate culture fostering initiatives have been implemented to mitigate integrity risks with the focus being on the procurement area. The survey and research focus primarily on indirect material or non-production material. The subject of procuring components for final products has been sufficiently researched and its results published, especially in the automotive industry. The field of non-production material in comparison is playing a minor role although the spectrum of commodities and complexity is much higher than for component procurement or procurement of direct material. The thesis recommends an implementation guide for risk mitigating strategies in the form of processes and tools targeting fraud-prone procurement sub-processes. Proposed solutions need to put into consideration the fact that they must be readily available, impactful and proven. In addition, the proposed path to prevent fraud in procurement has considered the size of a company as determining factor for feasibility and affordability.